The Financial Close Process in German Corporations: Developing and Testing A Theoretical Model - Ashutosh Deshmukh; Maximilian Holzmeier (Journal of Accounting and Management Information Systems (JAMIS), 2023)
Research Question- What variables affect the days to financial close for corporations? Motivation- The tightening of reporting deadlines, new disclosure requirements such as using XBRL, and ever-increasing demand for high-quality financial information have increased attention to the financial close process. However, academic research is sparse in this area, and no paper has developed a theoretical model for the financial close process. Data- The data were collected from 55 German corporations in different industries. Tools- The questionnaire survey was used to collect the data, which was analyzed via multiple regression techniques. Findings- The statistical analysis indicates that the model's overall fit is high. The technological challenges and technological strengths come out to be the most important explanatory variables. However, the peripheral challenges and the number of consolidating entities have a counterintuitive result; those variables are negatively related to the days to close. Also, size was significantly positively associated with days to close. Based on the practitioners' opinions, we also identified the critical best practices in the accounting and technology areas. Contribution- The contributions of this paper are as follows. We develop a pioneering theoretical model for the financial close process based on academic and practitioner research. The model indicates a high explanatory power indicating that our research has further potential. The technological abilities of the organizations are the most significant determinants of the days required for the financial close process. Finally, the rank-ordered best practices should provide guidance to the consultants and accountants. The broader implications for further research are also discussed.
Keywords: M41; 650; the financial close process; days to close; last mile of finance; best practices in the financial close process